Profile of Students of Sports Science Study Programs in 2023 - Marnex Willner Standing (Researchparks Publishing, 2023)
Cardiopulmonary endurance is the ability of the heart, lung and blood vessel systems to function optimally while carrying out daily activities for a long time without experiencing significant fatigue. This research focused on